Pedagogical, Methodological and Didactic Bases Applied to Teaching Handball: A Literary Review (2017-2022) - Espoz-Lazo, Sebastián; Hinojosa-Torres, Claudio; Farías-Valenzuela, Claudio; Giakoni-Ramírez, Frano; del Val Martín, Pablo; Valdivia-Moral, Pedro (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Pedagogy, methodology, and didactics are fundamental in the development of handball because they promote the integral formation of individuals through multi-variable practices that are effective for the acquisition of technical-tactical skills. However, most studies on handball focus on performance, injury prevention, and match analysis. Therefore, the aim of this work is to identify, consolidate, analyze, and describe the methodological, pedagogical, and didactic strategies used in the training of handball. A search was carried out in WoS following the PRISMA guidelines, including articles from 2017 to 2022 in English, Spanish, and Portuguese, including only research in social and educational sciences. Articles examining the effectiveness of teaching and learning in handball and technical and tactical training methods such as methodological designs were selected, excluding other types of documents. Of the 19 selected documents, most are published in English and are carried out mainly in Brazil and Spain. These are divided into three categories: training processes, evaluation, and use of methodological instruments. The results show significant differences in the methods used. It is concluded that research on the methodology, didactics, and pedagogy applied to the teaching and training of handball is little explored. Most of the reviewed studies have been carried out in Brazil and Spain using the handball elite as research subjects, suggesting that there are other populations that could benefit from methodological, didactic, and pedagogical alternatives adapted to their contexts and realities.